MODEL PENTAHELIX DALAM PENINGKATAN KUALITAS PENDIDIKAN DI KABUPATEN SUKA BUMI - Muhammad Rifki Habibie Nur Azmi; Tri Yuniningsih; Endang Larasati S. (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
The government is obliged to present a quality education to all its people without exception as a form or function of public service. In Law Number 20 of 2003 concerning the National Education System (UU SISDIKNAS) stipulates that every Indonesian citizen has the right and obligation to obtain educational services through the government's Compulsory Schooling program for 12 years. But in fact, until now there are still many regions in Indonesia which are considered to have low quality education, one of the areas with low quality education is Sukabumi Regency. The Sukabumi Regency Government certainly cannot run alone without the support or cooperation of other parties. Various institutions must collaborate with each other to improve the quality of education, namely collaboration between the government, the private sector, academia, the community, and the media in an effort to improve the quality of education in the District. This study uses conclusions from planning theories originating from Blackman with a qualitative descriptive approach assisted by the use of ATLAS.ti software to analyze the research results. The data collection techniques used were observation, documentation, and interviews with key informants, namely the head of the administrative division of the Education Office of West Java Province region 5. The results showed that there were 5 actors involved in efforts to improve the quality of education in Sukabumi Regency, but collaborative efforts were still has not run optimally because there is no continuation of the program from secondary actors, so that in order for the efforts to be carried out to run effectively, the government feels the need to cooperate formally with secondary actors.